Prevention of thrombogenesis in the extracorporeal circuit of hemodialysis with a low molecular heparin: standardization of the dosage with a better hemorrhagic risk/effectiveness ratio. - Barata, J D (1992)
To test the efficacy and safety of a low molecular. Weight heparin (LMWH)--Fraxiparine, for hemodialysis (HD) anticoagulation, compared with conventional heparin (H) or serum lavage without other anticoagulation (L).Prospective controlled study.Twenty-nine consecutive patients referred for dialysis in a tertiary care hospital were divided in 3 groups A, B and C, each group A and B patient submitted to 2 dialysis, AI and AII, BI and BII. Group A--n = 10, no bleeding risk, single needle technique, blood flow (Qb) less than 200 ml/min. HD-AI used LMWH 10,000 U pre-HD, HD-AII used H for an ACT 1.5 to 2 times baseline; group B--n = 10, high bleeding risk, double needle dialysis, Qb--200 to 300 ml/min. HD-BI used LMWH 5000 U pre-HD, and HD-BII used only L; Group C--n = 9, no bleeding risk, Qb less than 200 ml/min, all received LMWH 5000 U pre-HD. A semiquantitative screening was done in each dialysis for the presence of dialyser or venous chamber clots, APTT and Anti Xa activity were measured every 30 min., as well as pre and post-dialysis Hb, Htc, and platelets.APTT didn't rise significantly during HD with LMWH in contrast with the AII group with H (32.2 +/- 7.1 vs 63 +/- 25.8, p less than 0.05). The APTT levels in all dialysis with LMWH were identical to BII dialysis With L. Anti xa activity had an early peak at 30 to 60 min. With LMWH (0.62 +/- 0.45 em AI) and a late one at 180 min with H (0.39 +/- 0.2). There was no significant differences between pre and post-dialysis corrected platelet counts, but the lavage group showed the greater decrements (-20% +/- 24). In all the 49 dialysis we had 5 cases of complete clotting of the blood circuit, all of them in the lavage group C. No patients with high risk of hemorrhage had any bleeding increment.LMWH prevents clotting as effectively as H, in low doses of 5000 anti Xa units it doesn't interfere with PTT and is far more effective than HD with serum lavage in patients with bleeding risk and/or low blood flow in the dialysis circuit.